IMPLEMENTATION OF LAW NUMBER 23 2002 ON REGARDING CHILD PROTECTION (STUDY ON EXPLOITATION OF UNDERAGE CHILD IN EFFORT OF BRICK MAKING OF SUB DISTRICT OF TENAYAN RAYA PEKANBARU) - Herlin Carolina; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Pekanbaru is one of the of the big cities in Indonesia is the center of economic, social and cultural activity. However, with the development of newborn city. The emerging problem is the growing inequality or inequality of rights in the distribution of income between different opinion groups, between urban and rular areas. This also means that the rapid economic growth has not been successful in overcoming poverty problems such as underage labor as laborers. The problem in this research is how the Implementation of law Number 23 2002 on Regardi Child Protection (Study On Exploitation of Underage Child in Effort of Brick Making if Sub District of Tenayan Raya Pekanbaru) and What factors that hinder the implementation of the policy. As for the purpose of this research is to know and analyze the the Implementation of law Number 23 2002 on Regardi Child Protection (Study On Exploitation of Underage Child in Effort of Brick Making if Sub District of Tenayan Raya Pekanbaru) and know and analyze the implementation of the policy.The concept of the theory that that the writer uses is the policy and the policy implementation. And the theory used is the theory of Grindle with two variables: the contents of policy and implementation environment. This study uses qualitative research methods with a descriptive data assessment. In collecting the data, the writer uses interview, observation and documentation. Using the key informants as the source of information.The results of this study showed that the the Implementation of law Number 23 2002 on Regardi Child Protection (Study On Exploitation of Underage Child in Effort of Brick Making if Sub District of Tenayan Raya Pekanbaru) has not run optimally. The impeding factors in the implementation of child protection policies are human resources of policy actors, lack of compliance and responsiveness of the community regarding child protection policies.Keywords: Implementation of policy and Child Protection